Parental holding terhadap distress prosedur terapi intravena (IV) pada anak di rumah sakit - Tirtayanti, Sri; Zega, Marizka Putri Wati (Holistik Jurnal Kesehatan, 2025)
Background: Hospitalization is an unpleasant experience and can cause stress, both for children and parents. Children are a vulnerable group who often experience anxiety when undergoing medical procedures, especially when intravenous (IV) therapy is performed. This experience often makes the condition feel foreign, frightening, and triggers high levels of anxiety in children. Fear of needles, physical discomfort, and separation from parents or a comfortable environment are some factors that can increase children's anxiety when invasive procedures are performed. Parental holding is an approach that applies the process of physical and emotional involvement of patients, in the form of hugs/embraces given with full attention and affection by parents to their children when invasive procedures are performed. Purpose: To determine the effect of parental holding on distress of intravenous (IV) therapy procedures in children in the hospital. Method: Quantitative research with quasi-experimental design using post-test control group design. The sampling technique used accidental sampling and obtained 50 participants. How to measure the level of anxiety using a checklist face anxiety scale sheet and analyzed using the Mann Whitney test. Results: The pre-test anxiety score in the intervention group, the score range was 4-6 with a mean value of 5.67 and a standard deviation of 0.569. However, the anxiety score decreased during the post-test to 2-3 with a mean value of 2.92 and a standard deviation of 0.277. In the control group, the pre-test anxiety level score was obtained in the range of 2-6 with a mean value of 3.46 and a standard deviation of 1.262, while the post-test score range was 4-6 with a mean value of 5.41 and a standard deviation of 0.700. The significance value (Sig.2-tailed) was obtained at 0.000 (≤ 0.05) so that Ho was rejected and Ha was accepted. Conclusion: There is an effect of parental holding on the distress of intravenous (IV) therapy procedures in children in the hospital. Parental holding should be done by parents to children who are being treated in hospital through hugs, so that it can foster a sense of comfort and will speed up the healing process in children.   Keywords: Children; Intravenous (IV) Distress; Parental Holding.   Pendahuluan: Hospitalisasi merupakan pengalaman tidak menyenangkan yang dapat menyebabkan stress, baik anak-anak maupun orang tua. Anak merupakan kelompok rentan yang seringkali mengalami kecemasan pada saat menjalani prosedur medis, khususnya saat pemberian terapi intravena (IV). Pengalaman ini yang seringkali membuat kondisi terasa asing, menakutkan, dan memicu tingkat kecemasan yang tinggi pada anak. Ketakutan terhadap jarum, perasaan ketidaknyamanan fisik, dan pemisahan dari orang tua atau lingkungan yang nyaman adalah beberapa faktor yang dapat meningkatkan kecemasan anak saat prosedur invasif. Parental holding adalah pendekatan yang menerapkan proses pelibatan fisik dan emosional pasien, berupa pelukan/dekapan yang diberikan dengan penuh perhatian dan kasih sayang oleh orang tua kepada anaknya selama prosedur invasif. Tujuan: Untuk mengetahui pengaruh parental holding terhadap distress prosedur terapi intravena (IV) pada anak di rumah sakit. Metode: Penelitian kuantitatif dengan desain quasi eksperimental menggunakan post-test control group design. Teknik pengambilan sampel menggunakan accidental sampling dan didapatkan sebanyak 50 partisipan. Cara mengukur tingkat kecemasan menggunakan lembar checklist faces anxiety scale dan dianalisis menggunakan uji mann whitney. Hasil: Skor kecemasan pre-test pada kelompok intervensi, rentang skor 4-6 dengan nilai mean sebesar 5.67 dan standar deviasi 0.569. Namun, skor kecemasan menurun ketika post-test menjadi 2-3 dengan nilai mean 2.92 dan standar deviasi 0.277. Pada kelompok kontrol, diperoleh skor tingkat kecemasan pre-test pada rentang 2-6 dengan nilai mean sebesar 3.46 dan standar deviasi 1.262, sedangkan rentang skor post-test  4-6 dengan nilai mean 5.41 dan standar deviasi 0.700. Diperoleh nilai signifikansi (Sig.2-tailed) 0.000 (≤ 0.05), maka Ho ditolak dan Ha diterima. Simpulan: Terdapat pengaruh parental holding terhadap distress prosedur terapi intravena (IV) pada anak di rumah sakit. Parental holding sebaiknya dilakukan oleh orang tua kepada anak yang dirawat di rumah sakit melalui dekapan, sehingga menumbuhkan rasa nyaman dan akan mempercepat proses penyembuhan pada anak.   Kata Kunci: Anak; Distress Intravena (IV); Parental Holding.